Effects of different application ratios of biochar-organic compound fertilizers and chemical fertilizers on soil nutrition content and yield of maize - Zheng Zhang; Xiangzhe Huang; Shuwen Qin; Muhammad Azeem; Hongqin Wang; Shoujun Yang (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Overuse of traditional chemical fertilizers may result in environmental pollution and a decrease in the quality of farm produce. By contrast, applying biochar-organic compound fertilizers can enhance soil structure, increase soil fertility, and mitigate pollution levels. This study explores the intricate mechanisms of the combined application of biochar-organic compound fertilizers and chemical fertilizers on soil chemical properties and corn growth. The aim is to elucidate the theoretical foundations supporting the widespread adoption of biochar-organic compound fertilizers. A total of 6 treatments were set up, among which the CK treatment did not apply fertilizer, the CF treatment used bovine excrement organic fertilizer combined with chemical fertilizer, the T1 to T4 treatments used biochar-organic compound fertilizers and replaced 40%, 60%, 80%, and 100% bovine excrement organic fertilizer combined with chemical fertilizer. The results showed that applying biochar-organic compound fertilizers enhanced the slow-release properties of soil available nutrients, increased corn yield, and improved grain quality. Notably, when biochar-organic compound fertilizers were employed instead of 100% bovine excrement organic fertilizer, the yield surpassed that of other treatments, exhibiting a remarkable 9.30% increase compared to the CF treatment. Through comprehensive analysis, it was determined that using biochar-organic compound fertilizer to replace 60% of bovine excrement organic fertilizer is a scheme that can balance both fertilizer efficacy and cost and is recommended to farmers. This research can contribute to promoting the green transformation of agriculture and help achieve the goal of "carbon neutrality".